Pengaruh Model Pembelajaran Problem Solving Terhadap Kemampuan Pemecahan Masalah Matematis Siswa Kelas VIII SMPN 1 Sakra - Wahyu; Syahrul Azmi; Nourma Pramestie Wulandari; Sri Subarinah (FKIP Universitas Mataram, 2024)
This study aims to determine the influence of the problem solving learning model on the mathematical problem-solving ability of grade VIII students of SMPN 1 Sakra. This type of research is an experiment with a posttest only control design to measure students' problem-solving skills. The research sample consisted of two randomly selected classes, namely class A (experiment) taught with a problem-solving learning model and class B (control) with a direct learning model. The results showed that the average posttest score in the experimental class was 75.06 higher than that of the control class which was 66.72, as well as the completeness of the experimental class was higher than that of the control class. The average was significantly different because the results of the t-test with an independent sample were obtained at a significant level of 5%. The results of the effect size test obtained were 0,54 (in the medium category), showing that the problem solving model was quite effective in improving students' mathematical problem solving skills.